Designing for Maintainability: Maintenance Considerations in Sustainable High-Rise Office Design in Tropical Nigeria - Sani, Aisha Muhammad; Sagada, Musa Lawal; Yakubu, Kashim Ibn; Tijjani, Ishaq Nuhu; Aule, Thomas Terna (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study explores the integration of maintenance design features in the planning and design of high-rise office buildings, using a proposed office complex in Kano, Nigeria, as a case study. The research identifies a critical gap in architectural practice, where maintenance considerations, such as facade access, material durability, environmental responsiveness, and building form simplicity, are often overlooked during design stages. Through a review of literature, case studies, and practical design applications, the study highlights that architects frequently prioritise aesthetics and functionality without embedding maintenance solutions, leading to increased lifecycle costs and operational challenges for facility managers. The findings align with existing research advocating for maintenance-inclusive design approaches to enhance building sustainability and user safety. The study underscores the need for policymakers, architects, and stakeholders to mandate maintenance design integration as part of the building approval process. It further provides practical recommendations for material selection, environmental alignment, and accessibility planning to foster long-term building performance. The research concludes by emphasising the necessity for future studies to develop standardised maintenance design frameworks and expand investigations across different climatic zones. Overall, this study contributes to the growing discourse on sustainable architectural practices and offers valuable insights for improving high-rise building maintainability.